Enhanced Stability and Dermal Delivery of Hydroquinone Using Microemulsion-based System - Salimi, Anayatollah (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Hydroquinone (HQ), a famous anti-hyperpigmentation agent, suffers from several weaknesses such as instability due to rapid oxidation and insufficient skin penetration because of the hydrophilic structure. The aim of this research was to formulate, characterize and evaluation of in vitro skin permeability of HQ-loaded microemulsion (ME). Methods: HQ MEs were prepared by pseudoternary phase diagram method, the appropriate ratios of oil, s/c mixture, and water were chosen, and full factorial design was used with three variables at two levels for preparing eight formulations. The prepared MEs were evaluated regarding their droplet size, viscosity, pH, differential scanning calorimetry, stability, in vitro drug release, and in vitro skin permeability. Results and Discussion: The results showed that the mean droplet size range of ME samples was in the range of 7.05–79.56 nm and pH was 5.3–5.7, respectively. Viscosity range of MEs was 109–195 cps. Drug release profile showed that 90.51% of the drug released (ME-HQ-8) in the 24 h of the experiment. The kinetics of drug release from all selected MEs were approximately described by Higuchi model and showed prolonged release when compared to HQ solution. All ME formulations with different compositions and properties significantly increased flux and permeability coefficient from rat skin. Jss and Papp parameters in ME-HQ-2 formulation were 0.404 mg/cm2 h, 0.02 cm/h, and 4 times higher than those of control, respectively. The selective MEs have 99.9% HQ amount after 6 months storage. They have visually cleared and no any color changes, thus HQ MEs can could been protect drug for a long time without antioxidant. Conclusion: The present research established that the amount of components of water, oil, and S + C in ME formulation plays an important role in the physicochemical properties and permeability parameters. This study showed that any change in content and composition of MEs could be changed physicochemical properties and permeability parameters during drug permeation from ME samples. The studied MEs increased permeation rate and permeability coefficient through rat skin. Our results were showed that ME formulation could not be increase diffusivity of HQ in stratum corneum.